A Upf3b-mutant mouse model with behavioral and neurogenesis defects. Issue 8 (August 2018) - Huang, L; Shum, E; Jones, S; Lou, C-H; Dumdie, J; Kim, H; Roberts, A; Jolly, L; Espinoza, J; Skarbrevik, D; Phan, M; Cook-Andersen, H; et al.
Abstract Nonsense-mediated RNA decay (NMD) is a highly conserved and selective RNA degradation pathway that acts on RNAs terminating their reading frames in specific contexts. NMD is regulated in a tissue-specific and developmentally controlled manner, raising the possibility that it influences developmental events. Indeed, loss or depletion of NMD factors have been shown to disrupt developmental events in organisms spanning the phylogenetic scale. In humans, mutations in the NMD factor gene, UPF3B, cause intellectual disability (ID) and are strongly associated with autism spectrum disorder (ASD), attention deficit hyperactivity disorder (ADHD) and schizophrenia (SCZ). Here, we report the generation and characterization of mice harboring a nullUpf3b allele. TheseUpf3b -null mice exhibit deficits in fear-conditioned learning, but not spatial learning.Upf3b -null mice also have a profound defect in prepulse inhibition (PPI), a measure of sensorimotor gating commonly deficient in individuals with SCZ and other brain disorders. Consistent with both their PPI and learning defects, cortical pyramidal neurons fromUpf3b -null mice display deficient dendritic spine maturationin vivo . In addition, neural stem cells fromUpf3b -null mice have impaired ability to undergo differentiation and require prolonged culture to give rise to functional neurons with electrical activity. RNA sequencing (RNAseq) analysis of the frontal cortex identified UPF3B-regulated RNAs, including direct NMD target transcripts encoding proteins with known functions in neural differentiation, maturation and disease. We suggestUpf3b -null mice serve as a novel model system to decipher cellular and molecular defects underlying ID and neurodevelopmental disorders.